2009
DOI: 10.1038/npp.2009.7
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Memantine on Prepulse Inhibition

Abstract: Background Reduced prepulse inhibition (PPI) of startle provides evidence of deficient sensorimotor gating in several disorders, including schizophrenia. The role of NMDA neurotransmission in the regulation of PPI is unclear, due to cross-species differences in the effects of NMDA antagonists on PPI. Recent reports suggest that drug effects on PPI differ in subgroups of normal humans that differ in levels of baseline PPI or specific personality domains; here, we tested the effects of these variables on the sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 54 publications
2
57
2
1
Order By: Relevance
“…Based on this PPI enhancement, and reports of PPI-enhancing effects of ketamine and amantadine in healthy subjects (HS), we speculated that memantine would potentiate PPI in HS. Indeed, we reported that 20 mg memantine (po) enhanced PPI modestly across all HS (Swerdlow et al 2009) and that this effect was most robust among HS with low basal PPI levels (Fig. 1a), and among HS scoring high on personality scales for novelty seeking, sensation seeking, and disinhibition.…”
Section: Drug-enhanced Ppi As a Biomarker For Pact?mentioning
confidence: 79%
See 2 more Smart Citations
“…Based on this PPI enhancement, and reports of PPI-enhancing effects of ketamine and amantadine in healthy subjects (HS), we speculated that memantine would potentiate PPI in HS. Indeed, we reported that 20 mg memantine (po) enhanced PPI modestly across all HS (Swerdlow et al 2009) and that this effect was most robust among HS with low basal PPI levels (Fig. 1a), and among HS scoring high on personality scales for novelty seeking, sensation seeking, and disinhibition.…”
Section: Drug-enhanced Ppi As a Biomarker For Pact?mentioning
confidence: 79%
“…While NMDA antagonists are generally reported to disrupt PPI in rodents, PPI is actually increased in healthy subjects (HS) by NMDA antagonists such as ketamine (Duncan et al 2001;Abel et al 2003) and by the mixed NMDA antagonist/dopamine agonist, amantadine (Swerdlow et al 2002). In intact rats, we detected PPI-enhancing effects of memantine, using relatively short (10-30 ms) prepulse intervals (Swerdlow et al 2009). Based on this PPI enhancement, and reports of PPI-enhancing effects of ketamine and amantadine in healthy subjects (HS), we speculated that memantine would potentiate PPI in HS.…”
Section: Drug-enhanced Ppi As a Biomarker For Pact?mentioning
confidence: 83%
See 1 more Smart Citation
“…Interestingly, whereas NMDA systems have been implicated in the regulation of both PPI and MMN, the evidence linking reduced NMDA activity to deficits in PPI and/or MMN is not entirely straightforward. Thus, PPI is actually increased in healthy subjects (HS) by NMDA antagonists such as ketamine (Duncan et al, 2001;Abel et al, 2003), the low-to moderate-affinity NMDAreceptor antagonist, memantine (Swerdlow et al, 2009), and by the mixed NMDA antagonist/dopamine agonist, amantadine (Swerdlow et al, 2002b). Although MMN has been reported to be reduced in HS by ketamine (Umbricht et al, 2000;Umbricht et al, 2002), it has also been shown to be increased by memantine (Korostenskaja et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Memantine does not cause the sensory or dissociative symptoms produced by ketamine (Duncan et al, 2001;Abel et al, 2003;Umbricht et al, 2002), which might complicate the interpretation of changes in PPI and MMN. Doses (10 and 20 mg, po) were selected based on published reports in HS, which noted dizziness and other mild adverse reactions at higher doses (Swerdlow et al, 2009).…”
Section: Introductionmentioning
confidence: 99%